UPSR Math Learning Application for Improving Students’ Understanding - Md Yusoh, Muhammad Afif; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2022)
UPSR Math Learning Application is an application developed to help UPSR students, especially in Mathematics subjects at SK Bertam. There is no centralized application that collects mathematical resources and exercises that can make it easier for students to get info and brief notes quickly. With this application, students can get short notes and formulas quickly based on the selected topic. Reinforcement exercises as well as past UPSR questions are also available in this application module to assess students' understanding of a topic in this subject. Reinforcement exercises contain a certain level of questions, from easy questions to difficult questions so that students know their level of knowledge of certain topics. The Agile model is used as the development methodology of this application. The software used to develop this application is Android Studio as well as Firebase as a server. For the UPSR Math Gerak Gempur application, there are one user, who is a Year 6 student serves as an application user by answering the reinforcement training questions and selecting topics to be learned. This application will help students learn and understand a mathematic topic easily and effectively because of the attractive graphics and visuals in this application. In addition, students can also answer the questions found in this application in order to further strengthen their knowledge of certain topics. Students will also be clearer about a concept in mathematics with additional notes in this application.